Identification of two highly divergent catalase genes in the fungal tomato pathogen, Cladosporium fulvum - Bussink, H-J.; Oliver, Richard (2001)
Catalases of pathogenic micro-organisms have attracted attention as potential virulence factors. Homology-based screens were performed to identify catalase genes in the fungal tomato pathogen Cladosporium fulvum. Two highly divergent genes, Cat1 and Cat2, were isolated and characterized. Cat1 codes for a putative 566-amino-acid catalase subunit and belongs to the gene family that also encodes the mainly peroxisome-localized catalases of animal and yeast species. Cat2 codes for a putative catalase subunit of 745 amino acids and belongs to a different gene family coding for the large-subunit catalases similar to ones found in bacteria and filamentous fungi. Neither catalase had an obvious secretory signal sequence. A search for an extracellular catalase was unproductive. The Cat1 and Cat2 genes showed differential expression, with the Cat1 mRNA preferentially accumulating in spores and the Cat2 mRNA preferentially accumulating in response to external H2O2. With Cat2-deleted strains, activity of the Cat2 gene product (CAT2) was identified among four proteins with catalase activity separated on non-denaturing gels. The CAT2 activity represented a minor fraction of the catalase activity in spores and H2O2-stressed mycelium, and no phenotype was observed for Cat2-deleted strains, which showed a normal response to H2O2 treatment. These results indicate the existence of a complex catalase system in C. fulvum, with regard to both the structure and regulation of the genes involved. In addition, efficient C. fulvum gene-replacement technology has been established.